Nilai-Nilai Pendidikan Ekonomi Pada Tradisi “Bedeye” Dalam Sistem Perdagangan Tradisional Masyarakat Suku Sasak - Ali, Muhamad; Jailani, Huzain; Utomo, Danang Prio; Muhammad, Farhana (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This research investigates the economic education values contained within the tradition of "Bedeya," a traditional barter trading system practiced by the Sasak tribe community on Lombok Island, West Nusa Tenggara. Utilizing an ethnographic approach, this study explores the social, economic, and educational interactions intertwined within the practice of "Bedeya," revealing how this tradition facilitates the transmission of values and knowledge within the community. Data collection methods included participatory observation, in-depth interviews, and document analysis, with qualitative analysis techniques used to interpret the gathered data. The findings indicate that "Bedeya" is not only about the exchange of goods but also encompasses social and cultural learning, teaching values such as trust, fairness, and cooperation. This practice promotes social cohesion and maintains cultural identity amid modern socioeconomic changes. "Bedeya" plays a crucial role in the Sasak community's informal education system, providing life lessons relevant to the community's needs and challenges. This study offers new insights into the role of traditional trading systems in economic and social education, affirming the importance of preserving cultural practices as a vital source of learning. The findings provide a broader perspective on the integration of economic education in social and cultural life, underlining the need for a more holistic and community-based approach to economic education.